Pengetahuan dan Sikap Ibu Balita tentang Stunting - Pekabanda, Kartini; Toru, Veronika; Mila, Antonetha R H; Radandima, Ester (Poltekkes Kemenkes Kupang, 2022)
Background: Stunting is the biggest problem in the world and East Nusa Tenggara is one of the largest contributors to stunting. Nggaha Ori Angu Health Center in 2019 reached 26.1%, in 2020 reached 29.6%, and in 2021 decreased by 24.5%, Makamenggit Village in 2019 reached 33%, in 2020 decreased by 25.4%, in 2021 22.5%. Objective: This study is to determine the knowledge and attitudes of mothers of toddlers about stunting in Makamenggit Village, Work Area of ​​Nggaha Ori Angu Health Center, East Sumba Regency. Method: The type of research used in this study is a descriptive method that aims to determine the knowledge and attitudes of mothers of toddlers about stunting in Makamenggit Village, Nggaha Ori Angu Health Center Work Area. Results: Respondents of mothers of toddlers about stunting in the Nggaha Ori Angu Health Center work area consisting of 33 mothers of toddlers who have good knowledge as many as 3 people (9.1%), have sufficient knowledge as many as 14 people (42.4%), have less knowledge as many as 16 people (48.5%), have a good attitude 21 people (63.6%), who have less attitude 12 people (36.4%).